In-service piping inspection work-aid tool for process industries - Jia Chien, Lee; Hanida, Abdul Aziz; Hairunnisa, Osman (2021)
To develop framework for in-service piping inspection. To develop work-aid tool for in-service piping inspection. To validate te work-aid tool via case study